The Untruth Friendship and Starvation in Milne’s Winnie-the-Pooh - A. Arini Syahidah (Hasanuddin University, 2019)
This research aims to explore (1) the untruth friendship of Winnie-the-Pooh and (2) its advice for solving starvation of human being in Milne’s Winnie-the-Pooh. The research is a descriptive qualitative method with the support of semiotic approach. It uses smoke-fire concept in Pierce’s Index to look after Aristotle’s 8 characteristics of friendship. Those are explored through Winnie-the-Pooh novel as a primary data and Nicomachean Ethics, book of sociology, and dictionaries as a secondary data. The research discover the untruth is over 4 acts of characters. It keeps some friendship characteristics within. Therefore, those 4 acts directs a man to get a help of a friend.